Consensus study on factors influencing the academic entrepreneur in a middle-income country’s university enterprise - Alfred Austin Farrell; James Ashton; WitnessMapanga; Maureen Joffe; Nombulelo Chitha; Mags Beksinska; Wezile Chitha; Ashraf Coovadia; Clare L. Cutland; RobinL. Drennan; Kathleen Kahn; Lizette L. Koekemoer; et al. (My University, 2023)
Purpose – This study aims to ascertain the personal characteristics of a group of successful academic entrepreneurs in a South African university enterprise and the prevalent barriers and enablers to their entrepreneurial endeavour. Design/methodology/approach – The authors used a Delphi process to identify and rank the characteristics, enablers, barriers and behaviours of entrepreneurial academics, with a Nominal Group Technique applied to establish challenges they encounter managing their enterprise and to propose solutions. Findings – Perseverance, resilience and innovation are critical personal characteristics, while collaborative networks, efficient research infrastructure and established research competence are essential for success. The university’s support for entrepreneurship is a significant enabler, with unnecessary bureaucracy and poor access to project and general enterprise funding an impediment. Successful academic entrepreneurs have strong leadership, and effective management and communication skills. Research limitations/implications – The main limitation is the small study participant group drawn from a single university enterprise, which complicates generalisability. The study supported the use of Krueger’s (2009) entrepreneurial intentions model for low- and middle-income country (LMIC) academic entrepreneur investigation but proposed the inclusion of mitigators to entrepreneurial activation to recognize contextual deficiencies and challenges.
Keywords: Academic entrepreneurship, Academic entrepreneur, Entrepreneurial academic, Entrepreneurial intentions, LMIC, Delphi technique, Nominal group technique